2014
DOI: 10.5312/wjo.v5.i2.100
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative visual loss after spine surgery

Abstract: Perioperative visual loss (POVL) is an uncommon, but devastating complication that remains primarily associated with spine and cardiac surgery. The incidence and mechanisms of visual loss after surgery remain difficult to determine. According to the American Society of Anesthesiologists Postoperative Visual Loss Registry, the most common causes of POVL in spine procedures are the two different forms of ischemic optic neuropathy: anterior ischemic optic neuropathy and posterior ischemic optic neuropathy, accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 47 publications
1
61
0
3
Order By: Relevance
“…Subsequent reports established the causal relationship between increased intraocular pressure, decreased tissue perfusion, and perioperative visual loss (POVL). The rarity of this devastating complication has limited research [5] . The incidence of POVL after spine surgery ranges from 0.019% to 0.2%, with an increased risk during procedures involving prone positioning and in surgery for spinal deformity [6][7][8] .…”
Section: Opthamologic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent reports established the causal relationship between increased intraocular pressure, decreased tissue perfusion, and perioperative visual loss (POVL). The rarity of this devastating complication has limited research [5] . The incidence of POVL after spine surgery ranges from 0.019% to 0.2%, with an increased risk during procedures involving prone positioning and in surgery for spinal deformity [6][7][8] .…”
Section: Opthamologic Complicationsmentioning
confidence: 99%
“…There is also an increased risk in patients with comorbidities such as diabetes mellitus with end organ damage, coagulopathy, neurologic disorders, and paralysis [6] . Despite the absence of large prospective studies, several etiologies of POVL have been described, including anterior and posterior ischemic optic neuropathy (AION and PION), central retinal artery occlusion (CRAO), and cortical blindness [5] (Table 1). Other rare etiologies have also been reported, including POVL associated with acute closedangle glaucoma and amaurosis [9,10] .…”
Section: Opthamologic Complicationsmentioning
confidence: 99%
“…surgery [7]. Nickels et al have published a detailed analysis of POVL and clearly identified the risk factors and diagnoses where ischemic optic neuropathy seemed to be an important cause for the loss of vision with Anterior ischemic optic neuropathy (AION) being the more common one [3]. Significant blood loss also has been postulated as one of the mechanisms of visual loss [6] [8].…”
Section: Case Reportmentioning
confidence: 99%
“…The presence of bilateral disc oedema post non ocular surgery is not a very common condition but has been documented. Ischemic optic neuropathy, central retinal artery occlusion (CRAO) and cortical blindness have been noted as the possible final diagnoses [3]. The various risk factors identified are pre-existing diabetes, anaemia, age over 50, small cup disc ratio, intraoperative hypotension and prolonged operative time in the prone position [6].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…1,3 According to the American Society of Anesthesiologists (ASA) Postoperative Visual Loss Registry, most common causes of POVL in spine procedures are anterior and posterior ischemic optic neuropathy, both of which together account for 89% of the cases. 4,5,6 Retinal ischemia, cortical blindness, and posterior reversible encephalopathy are also observed in a minority of cases.…”
Section: Introductionmentioning
confidence: 99%